(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The aim of this work was to highlight the importance of chip thickness and type of wood for pulp production under the conditions of modern displacement sulphate cooking CBC (Continuous Batch Cooking). The main condition for optimal delignification process is the speed how the cooking chemicals come into contact with particular wooden fibres. This speed is given by chips quality – their dimensional, chemical and moisture uniformity. The optimal thickness of well-impregnable sapwood chips 3–4 mm and recommended thickness for chips prepared from hard impregnable heartwood 2–3 mm are very important for impregnation phase of CBC cooking. Different progress of impregnation of chips with thickness of 2–3 and 4–5 mm can be explained by different impregnation surface - the surface of fine chips was larger by 34.6%. There are no significant differences between a conventional cooking of chips with different size of the monitored wood species. Influence of the chip thickness and the type of wood on monitored parameters (yield, kappa number, amount of undercooks and REA) in CBC cooking was more evident, because of very high dry matter value of used chips. Regular impregnation and delignification of chips from hardwood mixture necessitate preparing of chips with thickness app. 3 mm from species with heartwood share greater than 50% (oak, black locust). The recommended ratio of sapwood and heartwood mixture is 4:1 (under realistic practice). The suitable combination of above stated parameters allows the production of high quality pulp from non-uniform chips.